Seasonal and spatial variations of greenhouse gas (CO2, CH4 and N2O) emissions from urban ponds in Brussels - Bauduin, T.; Gypens, N.; Borges, A.V. (Water research (Oxford), 2024)
•First survey of GHG emissions from Brussels ponds.•Small ponds are more subject to edge effects and have higher pCO2.•Macrophytes enhance methane production in ponds.•City center ponds have higher N2O emissions due to atmospheric deposition.•Brussels ponds emissions were equivalent to the carbon sink estimated for the urban green spaces. Freshwaters have been recognized as important sources of greenhouse gases (GHG) to the atmosphere. However, urban ponds have received little attention even though their number is increasing due to expanding urbanisation globally. Ponds are frequently associated to urban green spaces that provide several ecosystemic services such as cooling local climate, regulating the water cycle, and acting as small carbon sinks This study aims to identify and understand the processes producing GHGs (CO2, CH4, and N2O) in the urban ponds of the temperate European city of Brussels in Belgium. 22 relatively small ponds (0.1–4.6 ha) surrounded by contrasted landscape (strictly urban, bordered by cropland or by forest), were sampled during four seasons in 2021–2022. The mean ± standard deviation was 3,667 ± 2,904 ppm for the partial pressure of CO2 (pCO2), 2,833 ± 4,178 nmol L−1 for CH4, and 273 ± 662% for N2O saturation level (%N2O). Relationships of GHGs with oxygen and water temperature suggest that biological processes controlled pCO2, CH4 concentration and%N2O. However, pCO2 was also controlled by external inputs as indicated by the higher values of pCO2 in the smaller ponds, more subject to external inputs than larger ones. The opposite was observed for CH4 concentration that was higher in larger ponds, closer to the forest in the city periphery, and with higher macrophyte cover. N2O concentrations, as well as dissolved inorganic nitrogen, were higher closer to the city center, where atmospheric nitrogen deposition was potentially higher. The total GHG emissions from the Brussels ponds were estimated to 1kT CO2-eq per year and were equivalent to the carbon sink of urban green spaces. [Display omitted]